UPAYA PEMENUHAN KEBUTUHAN AIR BERSIH RUMAH TANGGA PADA DAERAH TERCEMAR PB DESA DUKUHSARI KECAMATAN JABON KABUPATEN SIDOARJO - Febri Meliawati; Iva Rustanti; Rachmaniyah . (GEMA LINGKUNGAN KESEHATAN, 2013)
Fulfillment of clean water should be related to consumption for human health. Thisresearch purposed to describes the fulfillment of household clean water which PB pollutedarea in Dukuhsari village Jabon district Sidoarjo Regency with 94 number.The sources of clean water in all household in Dukuhsari from ground water. Which theinfrastructure of supply 88,3% digging well. The drinks water sources is 79,8% tank water,with 55,3% manually transportation system. The storing facility is 58,5% permanent buildingwith cleaning Intensity once a week. All clean water supply used for shower, cloth washing,plant watering.Conclusion of this research are no household have water safe accessibility and no protecteddrinking water resources.Keywords: Fulfillment of clean water